Analisis Manajemen Kurikulum dan Pembelajaran Berbasis ICT - hasrul, Hasrul Muhibbin; Indah Puspa Haji (Jurnal Al-Hikam, 2023)
This study aims to describe the implementation of curriculum management and ICT-based learning at SD Negeri 2 Bengle, Wonosegoro - Boyolali. This type of research uses descriptive qualitative research. The implementation was carried out through the stages of preparing a research design, data collection, data analysis and preparation of a research report. Data collection instruments used observation and interview sheets as well as document study sheets. The data analysis technique uses a qualitative descriptive technique. The results of the study show that there are gaps in implementing curriculum and learning management, namely: 1) in planning, teachers have not made ICT-based lesson plans, 2) in the implementation stage, not all teachers use ICT-based learning media in class learning, there are only 3 teachers who use ICT-based media, 3) in supervision, the principal has not routinely supervised learning, evaluation and reporting. In addition to management obstacles, there are still obstacles outside of management, namely 1) lack of infrastructure, only 2 laptops and 2 LCDs available so that they must be used alternately, besides that there is no internet access because the school is located on the outskirts; 2) teacher competency is still low, out of 7 existing teachers, only 3 teachers are able to operate computers.